Transgenic Crops Emerging Trends and Future Perspectives - Sarwar Khan, Muhammad; Abdulla Malik, Kauser (IntechOpen, 2019)
Transgenic crops are the basis of modern agricultural biotechnology. Traits impossible to introduce by conventional breeding techniques are tailored in crops using genetic manipulation and transformation approaches. Using the technology, agronomic and medicinal traits have been developed in plants. The pace of -omics with robust methods for gene discovery and genome sequencing and more recently the use of CRISPR/Cas and gRNA/Cas technologies have widened this field to improve the genetic makeup of crops. Identification of transformation events and biosafety assessment of the introduced traits are vital for stewardship and acceptability of transgenic crops.